Art business: features of creating and management - A. O. Aleeva (Путеводитель предпринимателя, 2022)
The article is devoted to what is necessary first of all for organizing a creative business. The author notes that not every entrepreneur manages to properly organize this type of company. To do this, you need to pay attention to at least 5 key parameters.  Analytical work has been carried out to study the difficulties in creating and managing a company that creates any art product — a physical goods or a service. Own methods of self–testing of the business owner and the general principle of selecting creative candidates are proposed.